Improving The Stability of GRP Routing Protocol - Turkan A. Khaleel; Ahmed M. Fadhil; RanaKh.Sabri (Engineering and Technology Journal, 2016)
More recent works aim at enhancing MANET performance, because of the multiple problems caused by the wireless transmission constraints. The problem that faces the routing protocol is to obtain the stable path with nodes movement. A route between a source to destination is called "stable" if it consists of mainly stable neighbors at each intermediate hops. In this paper, a Geographic Routing Protocol (GRP) algorithm was chosen as a MANET routing protocol to be modified for stability. A new protocol wasthen created called SGRP routing protocol which workslikethe GRP routing algorithm, but with some modification to obtain better link stability. The main objective of this research is to decrease the time delay caused by wireless network and enhance the network performance by selecting the best route in the set of available routes that will have the least distance and highest neighbor stability. The model for this research has been designed and simulated by using C/C++ language embedded in the OPNET Modeler 14.5 software package. The SGRP routing model has been compared with the original GRP protocol. Acceptable results have been obtained depending upon the performance of metrics (MANET delay, total packets dropped and Throughput). The average MANET Delay and total packets dropped during the use of SGRP have decreased, while the throughput was acceptable.